Plasma procalcitonin and urine interleukin-8, neutrophil gelatinase–associated lipocalin, and calprotectin in the diagnostic process of a urinary tract infection at the emergency department - Stephanie J.M. Middelkoop; Robert Keekstra; L․Joost van Pelt; Greetje A. Kampinga; Anneke C. Muller Kobold; Jan C. ter Maaten; Coen A. Stegeman (International Journal of Infectious Diseases)
Objectives: This study aimed to assess the usefulness of plasma procalcitonin and urine IL-8 (interleukin-8), NGAL (neutrophil gelatinase–associated lipocalin), and calprotectin for diagnosis of urinary tract infections (UTIs) at the emergency department (ED). Methods: In adults presenting at the ED with UTI suspicion, biomarker performance was compared with that of routine diagnostics (urine dipstick, automated urinalysis). Patients with a urine catheter, leukopenia, or neither (standard) were analyzed separately. Results: A UTI was clinically diagnosed in 91 of 196 episodes (46.4%) (standard: 29/67 [43.2%]; catheter: 46/73 [63.0%]; leukopenia: 17/60 [28.3%]; four patients had both). Procalcitonin did not discriminate between UTI and no UTI. Urinary biomarker levels were elevated in UTI episodes (median, µg/mmol creatinine: NGAL, 7.8 vs 46.3; IL-8, 6.1 vs 76.6; calprotectin, 23.9 vs 265.4); the three subgroups also had higher levels. Biomarker cut-off values (90% sensitivity) showed low specificity (range 20.8-64.9%) and moderate accuracy (58.6-75.4%). The biomarkers performed similarly to routine diagnostics, except for patients with leukopenia, who exhibited nonsignificantly higher area under the curve values. All urinary biomarkers correlated positively with urine leukocyte count. Conclusion: Plasma procalcitonin could not accurately diagnose UTI. Urine IL-8, NGAL, and calprotectin showed no additional value relative to routine diagnostics, except a minor improvement in patients with leukopenia. These urine biomarkers seem to predominantly reflect leukocyturia.